Relasi Kewenangan Pemerintah Pusat dan Pemerintah Daerah dalam Penataan Kawasan Metropolitan Jabodetabek-Punjur - Allan Fatchan Gani Wardhana; Ni’matul Huda (Jurnal Hukum IUS QUIA IUSTUM, 2022)
The arrangement concept and development of the Metropolitan Area poses as one of the most interesting issues relating to local government law. Although the Regional Government Law provides flexibility for local governments to regulate and manage their regional affairs, in the Metropolitan Areas however, the Central Government takes part in structuring the regulations and institutions. This study examines two issues, namely the regulation of Metropolitan Areas in Indonesia and the relation of authority between the Central Government and Regional Governments in the arrangement of the Jakarta-Bogor-Depok-Tangerang-Bekasi-Puncak-Cianjur Metropolitan Area. This study uses a normative juridical method. The results of the study conclude that first, regulations regarding Metropolitan Areas are spread across various instruments, namely Legislations, Government Regulations, Provincial Regulations, and Regency/City Regional Regulations. Second, in structuring the Jabodetabek Metropolitan Area, the Central Government still dominates, while the Regional Government only needs to carry out what is the will of the Central Government. This dominance can be seen in the aspects of regulatory formation and management of Metropolitan Areas. Key Words: Authority; central government; regional government; metropolitan area AbstrakKonsep dan perkembangan penataan Kawasan Metropolitan menjadi salah satu isu yang menarik terkait hukum pemerintahan daerah. Meskipun Undang-Undang Pemerintahan Daerah memberikan keleluasaan bagi pemerintah daerah untuk mengatur dan mengurus sendiri urusan pemerintahan daerah, namun dalam isu Kawasan Metropolitan, Pemerintah Pusat ikut andil untuk melakukan penataan regulasi dan kelembagaan. Penelitian ini mengkaji dua hal yaitu pengaturan mengenai Kawasan Metropolitan di Indonesia dan relasi kewenangan Pemerintah Pusat dan Pemerintah Daerah dalam penataan Kawasan Metropolitan Jakarta-Bogor-Depok-Tangerang-Bekasi-Puncak-Cianjur. Penelitian ini menggunakan metode yuridis normatif. Hasil penelitian menyimpulkan, pertama, bahwa pengaturan mengenai Kawasan Metropolitan tersebar di berbagai regulasi yaitu Undang-Undang, Peraturan Pemerintah, Peraturan Daerah Provinsi, dan Peraturan Daerah Kabupaten/Kota. Kedua, dalam penataan Kawasan Metropolitan Jabodetabek, Pemerintah Pusat masih mendominasi, sedangkan Pemerintahan Daerah tinggal menjalankan saja apa yang menjadi kehendak Pemerintah Pusat. Dominasi ini nampak pada aspek pembentukan regulasi dan pengelolaan Kawasan Metropolitan. Kata-kata Kunci: Kewenangan; pemerintah pusat; pemerintah daerah; kawasan metropolitan